Practical experiences in Moodle LMS - Lengyel, Péter (Acta Agraria Debreceniensis, 2008)
We use Moodle at the University of Debrecen, Business- and Agricultural Department since January 2007. Moodle is an open source Learning Management System. Learning Management System (or LMS) is a software package that enables the management and delivery of learning content and resources to students. Most LMS systems are web-based to facilitate "anytime, anywhere" access to learning content and administration. LMS tracks student progress in a course and indicates completions. At the least, learning management systems track individual student progress, record scores of quizzes and tests within an online learning program, and track course completions. Moodle has more and more function at our Department in education. At present, we work to introduce Moodle in our Faculty. Therefore, we took lessons for the tutors about the usage of the Moodle. Our aim to develop such a learning system, which is an integral part of educational process.